The impact of community health care services on the mental health of older adults in China - Xi Yang; Hailing Ke; Yuting Song; Honggu Han; Yuxiang Zhao; Saibo Shi (BMC Health Services Research)
Abstract Background Population aging is the predominant global demographic trend of the contemporary era. However, the mental health of many older adults is not as good as it could be. Ensuring the rights and well-being of older adults is crucial for achieving sustainable and healthy aging. Numerous countries have implemented healthcare integration services tailored to their unique contexts. In 2016, China initiated community health care services for older adults. Methods We used panel data derived from the China Health and Retirement Longitudinal Study from 2015 to 2018 and analyses were performed using STATA, version 17. Our study employed a difference-in-differences model to assess the association of community health care services with mental health of older adults and conducted a placebo test to assess the reliability of the difference-in-differences model estimations. Additionally, subgroup regression analyses were conducted to investigate whether community health care services exert differing effects on the mental well-being of older adults across subgroups by sex, age groups, and education level. Results Community health care services significantly improved depression levels and cognitive function in older adults. Notably, these services exerted a more pronounced effect on alleviating depression symptoms among male older adults and more positively affected cognitive function among female older adults. Additionally, the services demonstrated greater effectiveness in improving both depression levels and cognitive function among older adults with lower educational attainment, while maintaining positive impacts on younger older adults. Conclusions Community health care services played a crucial role in enhancing the mental health of older adults, with varying degrees of impact across demographic groups. Our study underscores the importance of such services in promoting healthy aging and provides a foundation for the further development of hierarchical community health care services. This development is conducive to advancing community health care services, enhancing the mental well-being, and fostering healthy aging for Chinese older adults.